Computer aided decoration of ceramic tableware - Chua, Chee Kai. (2009)
The objective of this research is to computerise, automate and integrate the processes involved in the decoration of ceramic tableware. Computer usage in the ceramic tableware industry has largely been confined to word processing, spreadsheets, database, payroll, inventory and statistical process control. CAD/CAM or Computer Aided Design and Computer Aided Manufacturing is slowly gaining ground in this industry. The relatively high speed of generating physical designs from conceptuaüsation using CAD/CAM and Rapid Prototyping have suggested their use for the decoration of ceramic tableware.